Radiation protection in paediatric radiology - Rehani, Madan (International Atomic Energy Agency, 2014)
This publication provides guidance to radiologists, other clinicians and radiographers/technologists involved in diagnostic procedures using ionizing radiation with children and adolescents, and should also be of value to medical physicists and regulators. It focuses on the measures necessary to provide protection from the effects of radiation using the principles established in the IAEA's International Basic Safety Standards for Protection against Ionizing Radiation and for the Safety of Radiation Sources (IAEA Safety Standards No. GSR Part 3 (Interim)), and the priority accorded to the area. The emphasis throughout is on the special requirements of paediatrics.